prove that sec∅/tan∅+cot∅/cosec∅=sin∅+cos∅
Answers
Answer:
Let ∅ be 'A'
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1=>(sinAcosA)/(sin²A + cos²A)
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1=>(sinAcosA)/(sin²A + cos²A)=> 1/[(sin²A/sinAcosA) + (cos²A/sinAcosA)]
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1=>(sinAcosA)/(sin²A + cos²A)=> 1/[(sin²A/sinAcosA) + (cos²A/sinAcosA)]=> 1/(tanA + cotA)
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1=>(sinAcosA)/(sin²A + cos²A)=> 1/[(sin²A/sinAcosA) + (cos²A/sinAcosA)]=> 1/(tanA + cotA)=> RHS
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1=>(sinAcosA)/(sin²A + cos²A)=> 1/[(sin²A/sinAcosA) + (cos²A/sinAcosA)]=> 1/(tanA + cotA)=> RHSLHS = RHS
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1=>(sinAcosA)/(sin²A + cos²A)=> 1/[(sin²A/sinAcosA) + (cos²A/sinAcosA)]=> 1/(tanA + cotA)=> RHSLHS = RHSHence Proved
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1=>(sinAcosA)/(sin²A + cos²A)=> 1/[(sin²A/sinAcosA) + (cos²A/sinAcosA)]=> 1/(tanA + cotA)=> RHSLHS = RHSHence ProvedHope this helps....:)
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1=>(sinAcosA)/(sin²A + cos²A)=> 1/[(sin²A/sinAcosA) + (cos²A/sinAcosA)]=> 1/(tanA + cotA)=> RHSLHS = RHSHence ProvedHope this helps....:)Smenevacuundacy and 40 more users found this answer helpful
Let ∅ be 'A'Given => (cosecA - sinA)(secA - cosA) = 1/(tanA + cotA)LHS=> (cosecA - sinA)(secA - cosA)=> (1/sinA - sinA)(1/cosA - cosA)=> [(1 - sin²A)/sinA][(1 - cos²A)/cosA]=> (cos²A/sinA)(sin²A/cosA)=> sinAcosA/1=>(sinAcosA)/(sin²A + cos²A)=> 1/[(sin²A/sinAcosA) + (cos²A/sinAcosA)]=> 1/(tanA + cotA)=> RHSLHS = RHSHence ProvedHope this helps....:)Smenevacuundacy and 40 more users found this answer helpfulTHANKS
rosariomividaa3 and 31 more users found this answer helpful
Step-by-step explanation:
Reason: Lipases can break large fat droplets into smaller ones." ... Lipases can digest fat in significant amounts only when large fat droplets are broken into tiny droplets to form a fina emulsion. Emulsification of fats by bile salts thus increases the lipase action on fats.
Assertion (A): Lipase helps in emulsification of fats.Reason (R)
People also search for
bile helps in
emulsification of fats in
lipase hydrolyses
fats and oils
what helps in
emulsification of fats
16 assertion a lipases help in emulsification of
fats reason r lipases hydrolyses fats and oils
emulsification of fats
is done by which organ
assertion lipase help in emulsification of
fats reason lipases hydrolyses fats and oils
assertion lipase help in emulsification of
fats reason lipase hydrolyzes fats and oils
- emulsification of large fat droplets
into small globules is performed by